Perancangan Aplikasi Antrean Online Pemeriksaan Ibu Hamil Menggunakan User Experience Lifecycle - Ariq Cahya Wardhana; Tio Fani; Nurul Adila; Kukuh Pramadito Raharjo (STMIK Budi Darma, 2020)
This research was aiming to produce an application design based on user experience. The research target to be achieved is the design of an online queue application for examining pregnant women using the User Experience Lifecycle (UXL). This study uses four stages of UXL, namely, analysis, design, prototype, and evaluation. The analysis produces application concepts consisting of flow models, work activity affinity diagrams, design requirements, and social models. The analysis phase is derived from questionnaire data distributed to 13 respondents. The design phase aims to design a persona, sketch, and storyboard. The prototype stage was developed based on the previous stage, producing a medium-fidelity prototype. Evaluations were carried out using the System Usability Scale (SUS) of 11 respondents producing a value of 76.46 or B (Good). Based on this, this research successfully used UXL for application design that has exceeded the minimum standard. Therefore, it is expected that the application design based on user experience will reduce the application developers' suggestions in designing the interface before moving to the production stage of the application.